Improved approximate analytical solution for generalised diodeequation - Abuelma’atti, M.T. (1992)
A mathematical function for representing the generalised normalised diode equation is presented. This function, being simple, accurate and, more importantly, continuous, provides solutions for the generalised normalised diode equation which are in excellent agreement with numerical calculations